Karakteristik Peserta Didik Perspektif Imam Ibnu Jamaʿah: Studi Kitab Tadzkirah Al-Sāmiʿ wa al-Mutakallim fī al-ʾAdab Al-ʿĀlim wa Mutaʿallim karya Imam Badruddin Ibnu Jamāʿah - Maryono Maryono (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2020)
Students who are objects in the educational process are the main pillars in achieving educational goals. In this paper describes the "Characteristics of Students in the Perspective of Imam Ibnu Jamaʿah", through his phenomenal book adzkirah Al-Sāmiʿ wa al-Mutakallim fī al-ʾAdab Al-ʿAlim wa Mutaʿalim. The research method used is qualitative noninteractive because the data source is in the form of documents, not direct data from people in their natural environment. The data analysis used is content analysis, which is research that is in-depth discussion of the content of written information. Imam Ibnu Jamaʿah in Tadzkirah Al-Sāmiʿ wa al-Mutakallim fī al-ʾAdab Al-ʿAlim wa Mutaʿalim mentioned several things that must be possessed by a student so as to make a character for them, including 2 parts, First; characteristics of yourself which include; Cleanse the heart of despicable morals. Improve intention by constantly fighting lust. Make the most of your youth. Has the nature of qana'ah. Managing time. Applying wara '. Second; towards teachers include; Asking Allah for the best choice in choosing a teacher. Obey the teacher's directions according to syar'i. Recognize his teacher's rights and services to him. Be patient with the teacher's attitude. Thank the teacher in all circumstances.